Production of a conjugate between the rK346 antigen from Leishmania infantum and the horseradish peroxidase C for the detection of rK346 antibodies - Rengifo-González, Juan; Medina-Mora, Yollyseth; Silva-Barrios, Sasha; Marquez-Contreras, María Elizabeth; Ruiz, María Tibisay; Cáceres, Ana J.; Concepción, Juan Luis; Quiñones, Wilfredo (Investigación Clínica, 2016)
It was designed and characterized a reporter system to be captured by an- tibodies bound to ELISA plates. The system was designed with the rK346 from Leishmania infantum, a highly antigenic and specific protein. The rK346 was coupled to the horseradish peroxidase C (HRPc) from Armoracia rusticana using glutaraldehyde or sulfo-SMCC. Glutaraldehyde conjugation was performed in two steps. Separation of conjugates was carried out using a Sepharose S-200 in size exclusion chromatography (SEC); fractions were analyzed via HRPc activity and through ELISA plates sensitized with polyclonal anti-rK346 IgG purified from rabbit serum. A heterogeneous population of conjugates rK346-HRPc was obtained with molecular weights ranging between 109.7 Ó 16.5 to 67.6 Ó 10.1 kDa; with rK346-HRPc stoichiometries of 1:2; 2:1; 3:1; and 2:2. Conjugation using sulfo-SMCC was carried out first by introducing -SH groups onto the HRPc using the SATA reagent and the antigen was modified with sulfo-SMCC during 45 min. Separation and analysis of conjugates was performed similarly as with glutaraldehyde, resulting in a heterogeneous population of conjugates rK346- HRPc with molecular weights between 150.5 Ó 22.6 to 80.0 Ó 12.0 kDa; with rK346-HRPC stoichiometries of 2:1; 1:2; 2:2; and 1:3, with an increased conjugation efficiency in comparison with glutaraldehyde. This enables sulfo-SMCC to be used as a potential reagent for coupling the antigen to the HRPc, to design an economic, specific and easy method to apply as a reporter system, available to assess individuals at risk and/or at early and late stages of visceral leishmaniasis.